Effect of opening and wall boundaries on CFD modeling for submarine landslide-ambient water-pipeline interaction. (September 2022) - Guo, Xingsen; Stoesser, Thorsten; Zhang, Cheng; Fu, Cuiwei; Nian, Tingkai
Highlights: A physical flume experiment is accurately reproduced using CFD modeling of submarine landslide-ambient water-pipeline interactions. The effect of boundary conditions (i.e., opening and wall boundaries) on impact forces on suspended and laid-on-seabed pipelines caused by submarine landslides is quantified. The mechanisms of boundary conditions on the interface contact (i.e., distributions of the velocity field, pressure field and streamlines around pipelines) of landslides impacting pipelines are explained. A method for determining boundary conditions is proposed to optimize the CFD modeling of submarine landslide-ambient water-pipeline interactions. Abstract: Submarine landslide-ambient water-pipeline interactions are receiving extensive attention in ocean engineering, especially the impact forces caused by landslides on pipelines. Computational fluid dynamics (CFD) approaches are widely used to obtain these forces; however, as necessary definite solution conditions, the boundary conditions of CFD modeling are challenging to reasonably determine. In this study, the relationship between the finite volume method (FVM) in CFD modeling and boundary conditions is presented, and a classic physical flume experiment is reproduced using CFD modeling, verifying the effectiveness of the established modeling. The quantitative effect of the opening and free slip wall boundaries under variable complex working conditions (i.e., Reynolds number, pipeline span height, landslide impact velocity, and landslide rheological model) is explored via a general geometry model. The evolution characteristics of impact forces on pipelines under different boundary conditions are given. The mechanism caused by impact force changes is explained through the distributions of the velocity field, pressure field and streamlines around pipelines. Furthermore, a method for determining boundary conditions is briefly proposed, providing a basis for optimizing the CFD modeling of submarine landslide-ambient water-pipeline interactions.